Kedudukan Hukum Internasional dalam Sistem Hukum Nasional - Ariadno, Melda Kamil (Indonesian Journal of International Law, 2008)
In every discussion regarding international law principles, the doctine of applicaion of treaties in national legal system, as usually reffered as the relaton between international law and national law, always becomes the major topic. States have its own way to determine the relation between two legal systems, as to consider which treaties would be directly applied in national legal system and which ones would need implementing regulations after its ratification.